(untitled) (Context: Journal of Interdisciplinary Studies, 2025)
This article examines models of the description and classification of the sciences among the Ottomans in the 15th century. It considers the importance of the works of Mehmed Şah Fenârîzâde, ʿAbd al-Raḥmān al-Bistāmī and Mollā Luṭfī for the classification of the sciences in the 15th-century Ottoman context. Different authors adopted distinct theoretical perspectives and methodological approaches to the subject. The analysis partly addresses the genre of unmūḏağ literature as a particular model for describing scientific disciplines, as well as certain phenomena related to the introduction of new methodological approaches and new ways of conceptualizing the notion of ʿilm within the Ottoman literary tradition of the period. The tendency to relativize certain scientific fields in particular types of literature could partially influence the development of some disciplines while contributing to the neglect of others. The struggle for dominance of a given educational paradigm depended on both the foundational principles upon which the relevant institutions were established and the literature selected and canonized during the formulation of curricula at the time of their founding.